ARI(1,1) Model for Predicting Covid19 in Indonesia - Pradana ratnasari, Nanda Rizqia (Indonesian Journal of Life Sciences, 2020)
Covid19 modelling is needed to help people understanding the distribution or pattern of the data and doing the prediction. The data used for modelling in this study was ‘confirmed cases’ of Covid19 in Indonesia recorded from March 2 to August 23, 2020. Model obtained from analysis was ARI(1,1) with estimated parameter 0.9859 and standard error 0.0114. Maximum Likelihood was the method conducted to estimate the parameters. The model was good to predict the actual data of Covid19 confirmed cases in Indonesia. Keywords: Covid19, autoregressive, prediction.